1988
DOI: 10.1111/j.1471-4159.1988.tb03063.x
|View full text |Cite
|
Sign up to set email alerts
|

A Two‐Dimensional Electrophoresis Study of Phosphorylation and Dephosphorylation of Chromaffin Cell Proteins in Response to a Secretory Stimulus

Abstract: Phosphorylated proteins of bovine chromaffin cells, radioactively labeled with [32P]orthophosphate, have been analyzed by two-dimensional polyacrylamide gel electrophoresis and autoradiography. Complex two-dimensional electrophoretograms were studied with the aid of computer-assisted image analysis (CAIA). A database map of 32P-labeled proteins was constructed; approximately 500 polypeptides have been detected, numbered, and characterized according to the intensity of labeling, molecular weight, and isoelectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 35 publications
(19 reference statements)
2
18
0
Order By: Relevance
“…Another strongly INA-labeled band is the one at 28 kDa (pI 5.3). C6td et al (13) observed high stimulus-induced phosphorylation in a protein running at 29 kDa (pI 5.7 and 5.9) and a band with essentially identical characteristics was found by Gutierrez et al (32). Similar situations obtain for our 34-(pI 4.8), 38-(pI 5.4), and 42-(pI 4.8-6.3) kDa components, all undergoing strong stimulus-induced INA labeling, for all of which there exists a close parallelism with values cited in the literature (13,27,32).…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Another strongly INA-labeled band is the one at 28 kDa (pI 5.3). C6td et al (13) observed high stimulus-induced phosphorylation in a protein running at 29 kDa (pI 5.7 and 5.9) and a band with essentially identical characteristics was found by Gutierrez et al (32). Similar situations obtain for our 34-(pI 4.8), 38-(pI 5.4), and 42-(pI 4.8-6.3) kDa components, all undergoing strong stimulus-induced INA labeling, for all of which there exists a close parallelism with values cited in the literature (13,27,32).…”
Section: Resultssupporting
confidence: 51%
“…C6td et al (13) observed high stimulus-induced phosphorylation in a protein running at 29 kDa (pI 5.7 and 5.9) and a band with essentially identical characteristics was found by Gutierrez et al (32). Similar situations obtain for our 34-(pI 4.8), 38-(pI 5.4), and 42-(pI 4.8-6.3) kDa components, all undergoing strong stimulus-induced INA labeling, for all of which there exists a close parallelism with values cited in the literature (13,27,32). While the nature of most of these proteins is unknown at present, this apparent correlation between phosphorylation and close interaction with the plasma membrane perhaps gives us an initial clue regarding at least one aspect of the exocytotic mechanism.…”
Section: Resultssupporting
confidence: 51%
“…Chromaffin cells were isolated from bovine adrenal glands by collagenase digestion, and they were further separated from the debris and erythrocytes by centrifugation on Percoll gradients as described previously (Gutierrez et al, 1988;Gil et al, 2002). The cells were maintained as monolayer cultures in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal calf serum, 10 mM cytosine arabinoside, 10 mM 5-fluoro-29-deoxyuridine, 50 U/ml penicillin and 50 mg/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…A number of observations suggest that conventional myosin II activity influences catecholamine secretion. For example, chromaffin cell stimulation induces the calcium-dependent phosphorylation of the regulatory subunit of myosin light chain (RLC) 1 (5)(6)(7), and as such, constitutes the basic mechanism for governing the interaction of non-muscular myosin II with actin (8). In addition, phosphorylation of non-muscle myosins by the specific enzyme myosin light chain kinase (MLCK), may be essential to this proteins role in secretion, because inhibition of MLCK by a variety of chemicals abrogates secretion in permeabilized (9 -12) or intact chromaffin cells (2).…”
mentioning
confidence: 99%